ALTERNATIVE ASSESSMENT: PORTFOLIO "CRADLE" IN CLT FOR ENGLISH IN NURSING INCREASING STUDENTS’ ACHIEVEMENT - MUNFADLILA, ASEF WILDAN; Febrijanto, Yoyok; Elli Kristanti, Erva (English Education:Journal of English Teaching and Research, 2019)
New forms of assessment are needed to replace traditional multiple-choice and other items that test lower-order skills. One alternative assessment in communicative language teaching (CLT) is portfolios. In portfolios, students collect assignments with specific goals that demonstrate the efforts, progress, and achievements in a particular area (e.g. mastery of English in nursing). “CRADLE” is acronym portfolios designed into 6 parts, namely Collecting, Reflecting, Assessing, Documenting, Linking, and Evaluating focusing procedures and documentation achievement in teaching English in nursing. This R&D aims to develop an assessment tool for learning English in nursing based on CLT adapted from Borg and Gall's method. The subjects involved 45 students, 2 teachers of English in nursing, 2 nursing experts, and 1 hospital practitioner who were concerned with teaching English in nursing. The results showed that students' understanding was sufficient category with an average score of 26.11 and the maximum score achieved by students was 32 as many as 10 students (22.2%), the majority of respondents were getting a score of 25. After intervention, the level of students’ understanding was obtained an average score of 27.22. The data analysis results of Wilcoxon Sign Rank Test was obtained p=0.020 and Z-score = -2,324. Giving intervention increased level of students’ understanding of 12 respondents (26.7%), decreasing understanding of 3 respondents (6.7%) and a constant understanding of 30 respondents (66.6%). The minimum score obtained by students after intervention was 19 and the maximum score was 36. In conclusion, the students had increasing understanding of English in nursing in order to develop assessment by maximizing students’ competency in CLT for English in nursing through alternative assessment of portfolios CRADLE. It can be used to build a comprehensive picture of what students can do in a second language.